Language Screening in 3-Year-Olds: Development and Validation of a Feasible and Effective Instrument for Pediatric Primary Care - Holzinger, Daniel; Weber, Christoph; Barbaresi, William; Beitel, Christoph; Fellinger, Johannes (Frontiers in Pediatrics, 2021)
Abstract (271 words) Objective: The study was aimed at evaluating the validity and feasibility of SPES-3 (Sprachentwicklungsscreening), a language screening in three-yerar-old children within the constraints of regular preventive medical check-ups. Methods: A four-component screening measure including parental reports on the child's expressive vocabulary and grammar based on the Mac Arthur Communicative Development Inventory and pediatrician-administered standardized assessments of noun plurals and sentence comprehension was used in a sample of 2044 consecutively seen children in 30 pediatric offices. One-hundred forty-four children (70 who had failed and 74 who had passed the screener) comprised the validation sample and also underwent follow-up clinical assessment. To avoid verification and spectrum bias multiple imputation of missing diagnosis for children who did not ungergo clinical assessment was used. Independent diagnosis by two experts blinded to the screening results were considered reference standard for diagnosing language disorder. Screening accuracy of each of the four subscales was analyzed using receiver operator characteristics (ROC) curves. Feasibility was assessed by use of a questionnaire completed by the pediatricians. Results:The two parental screening subscales demonstrated excellent accuracy with area under the curve (AUC) scores of .910 and .908 whereas AUC scores were significantly lower for the subscales directly administered by the pediatricians (.816 and .705). A composite score based on both parental scales (AUC = .946) outperformed single subscales. A cut off of 41.69 on a T-scale resulted in about 20% positive screens and showed good sensitivity (.878) and specificity (.876). Practicability, acceptability and sustainability of the screening measure were mostly rated as high. Conclusion: The parent-reported subscales of the SPES-3 language screener are a promising screening tool for use in primary prediatric care settings.